2005
DOI: 10.1007/s10096-005-0029-3
|View full text |Cite
|
Sign up to set email alerts
|

Favorable outcome of pneumonia due to Panton–Valentine leukocidin-producing Staphylococcus aureus associated with hematogenous origin and absence of flu-like illness

Abstract: Reported here is what is believed to be the first case of community-acquired pneumonia caused by a Panton-Valentine leukocidin-producing strain of Staphylococcus aureus in Spain. Although lung infections caused by S. aureus strains carrying this powerful leukocidin gene are associated with necrotizing pneumonia and high mortality, the previously healthy 28-year-old male reported here experienced a good clinical course and recovery. It is thought that the hematogenous origin of the infection, the patient's lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Ninety-two cases of severe S. aureus CAP were reported in 70 articles during the period from 1995 to 2009 from North America (35 cases, 38.0%) [2,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42], Europe (40 cases, 43.5%) [1,7,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74], Asia (11 cases, 12.0%) [75,76,77,78,79,80,81,82], and Australia (6 cases, 6.5%) [83,84,85,86,87,88] (table 1). Data on outcomes were available for 91 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ninety-two cases of severe S. aureus CAP were reported in 70 articles during the period from 1995 to 2009 from North America (35 cases, 38.0%) [2,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42], Europe (40 cases, 43.5%) [1,7,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74], Asia (11 cases, 12.0%) [75,76,77,78,79,80,81,82], and Australia (6 cases, 6.5%) [83,84,85,86,87,88] (table 1). Data on outcomes were available for 91 patients.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting, however, that laboratory-confirmed viral infections were only reported in 10 cases. A study [50] reported 1 case of MRSA CAP with a favorable outcome associated with the absence of flu-like illness. It is thought that the absence of a prior flu-like infection probably precluded massive infestation and may explain the absence of absolute neutropenia and satisfactory evolution in this case.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the isolates obtained from patients with episodes of deep-seated skin abscesses or furuncles in outbreak settings frequently exhibit methicillin resistance, whereas sporadic cases usually show methicillin sensitivity [4,8]. The prevalence of PVL-positive S. aureus strains in Spain is very low; there are only 12 reported cases of pneumonia or skin infections due to PVL-positive S. aureus that were methicillin-resistant [18][19][20]. A Spanish multicentric methicillin-resistant S. aureus prevalence study did not reveal any PVL-positive isolates [21].…”
mentioning
confidence: 99%